One Pot Synthesis and Antimicrobial Evaluation of 8-Substituted-2,5-dihydro-2-(2-nitrophenyl/4-nitrophenyl)-4-(2-thienyl)-1,5-benzothiazepines - Kandalkar, Madhuri; Sharma, Priyanka (Asian Journal of Chemistry, 2023)
The reaction of an α,β-unsaturated heterocyclic ketone, 3-(2-nitrophenyl/4-nitrophenyl)-1-(2-thienyl)-2-propenone (3a-b) with 5-substituted-2-aminobenzenethiols (4a-d) with substituent -CH3, -Cl, -F and -Br was carried out in dry methanol containing trifluoroacetic acid (TFA) in catalytic amount as well as by swirling for 20 min in diethyl ether at room temperature. The yields of the products, 8-substituted-2,5-dihydro-2-(2-nitrophenyl/4-nitrophenyl)-4-(2-thienyl)-1,5-benzothiazepines (5a-h), ranged from 60% to 75% by first method and 65% to 85% by second method. The synthesized compounds have been characterized by micro-estimation of C, H, N and 1H NMR, 13C NMR as well as mass spectral studies. All the synthesized compounds are tested for biological efficacy against, Gram-positive bacteria, Staphylococcus aureus, Gram-negative bacteria Escherichia coli and fungi, Candida albicans. All of the compounds demonstrated effective antibacterial and antifungal activities.